Effect of vitamins D and e on the Proliferation, viability, and differentiation of human dental pulp stem cells: an in vitro study (2020)
ntroduction. The aim of the present study was to determine the effects of vitamins D and E on the proliferation, morphology, and differentiation of human dental pulp stem cells (hDPSCs). Methods. In this in vitro experimental study, hDPSCs were isolated, characterized, and treated with vitamins D and E, individually and in combination, utilizing different doses and treatment periods. Changes in morphology and cell proliferation were evaluated using light microscopy and the resazurin assay, respectively. Osteoblast differentiation was evaluated with alizarin red S staining and expression of RUNX2, Osterix, and Osteocalcin genes using real-time RT-PCR. Results. Compared with untreated cells, the number of cells significantly reduced following treatment with vitamin D (49%), vitamin E (35%), and vitamins D + E (61%) after 144 h. Compared with cell cultures treated with individual vitamins, cells treated with vitamins D + E demonstrated decreased cell confluence, with more extensive and flatter cytoplasm that initiated the formation of a significantly large number of calcified nodules after 7 days of treatment. After 14 days, treatment with vitamins D, E, and D + E increased the transcription of RUNX2, Osterix, and Osteocalcin genes. Conclusions. Vitamins D and E induced osteoblastic differentiation of hDPSCs, as evidenced by the decrease in cell proliferation, morphological changes, and the formation of calcified nodules, increasing the expression of differentiation genes. Concurrent treatment with vitamins D + E induces a synergistic effect in differentiation toward an osteoblastic lineage.